How Critical is the Duration of the Sampling Scheme for the Determination of Half-Life, Characterization of Exposure and Assessment of Bioequivalence? - Philippe Colucci; Jacques Turgeon; Murray P. Ducharme (Frontiers Media S.A., 2011)
In noncompartmental analysis, poor characterization of the terminal elimination rate constant (Kel) will lead to biased results for half-life and total exposure (AUCinf), providing incorrect relative bioavailability and bioequivalence conclusions. We set out to determine if the sampling scheme duration was crucial for proper half-life and AUCinf determination. Profiles for 1000 subjects were simulated with a sampling scheme covering five half-lives. Concentrations were gradually removed from the end of the profile to determine if precision and bias in the half-life and AUCinf values were affected. Additionally, 30 bioequivalence studies were simulated to determine the influence of unreliable AUCinf PK parameter on BE conclusions. Precision and bias became unacceptable for AUCinf and half-life if Kel was not determined with a sampling scheme covering at least 2 and 4 half-lives, respectively. Bioequivalence conclusions also deteriorated if unreliable PK parameters were maintained. Sampling scheme duration is important when calculating noncompartmental parameters. In conclusion, sampling scheme duration should be at least 4 times the average measured half-life in order to have confidence in the reported half-life values. Additionally, individual subject's pharmacokinetic parameters should be removed from the pivotal statistical analysis when their associated calculated half-life is longer than half of the total sampling interval. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.